Consumo alimentar segundo a classificação NOVA, alterações da pressão arterial e incidência de hipertensão em adultos da Coorte de Universidades Mineiras (CUME) - Katiusse Rezende Alves (2020)
Background: Hypertension is an important public health problem due to its high magnitude once it is the most relevant risk factor for cardiovascular diseases (CVD), the main cause of disability and death worldwide. Unhealthy eating habits are one of the most important determinants for increasing blood pressure (BP) and the development of hypertension. This relationship has been studied using pre-defined scores or food classification, which mix both healthy and unhealthy foods in the same group. In order to overcome this problem, the NOVA classification was proposed in 2009. It separates foods according to the degree of processing into: unprocessed/minimally processed foods and processed culinary ingredients (U/MP/PCI); processed foods (PF); ultra-processed foods (UPF). Objective: To analyze food consumption according to the degree of processing of adults in the Minas Gerais University Cohort (CUME) and its association with changes in BP and the incidence of hypertension. Methods: Longitudinal study with 2,496 graduates from federal universities in the State of Minas Gerais that participated in the baseline (March to August 2016) and the first follow-up wave (March to August 2018) of the project (rate retention = 80%). At the baseline, participants answered a comprehensive online questionnaire with questions about lifestyle, sociodemographic, anthropometric, biochemical and clinical data, individual and family reported morbidity, use of medications and food consumption. In the follow-up, they answered a shorter online questionnaire about changes in lifestyle, eating habits and health conditions since the first data collection. The focus was on the incidence of diseases. The exposure was food consumption by food groups according to NOVA. The outcomes were: a) changes in systolic (SBP) and diastolic (DBP) blood pressures over time: a.1) continuously (e.g., SBP in follow-up - SBP at baseline) or a.2) categorized (maintained, decreased, increased); b) incidence of hypertension assessed by the criteria of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC), adopted in Brazil, and the one of American College of Cardiology/American Heart Association (ACC/AHA). Independent associations between exposure and outcomes were verified using appropriate multivariate statistical analysis techniques: a) BP changes continuous variables) = linear regression models; b) BP changes (categorical variables) = multinomial regression models; c) incidence of hypertension = Poisson regression models. Results: At baseline, SBP and DBP means were 115.6 mmHg and 75.2 mmHg and in the follow-up they were 115.3 mmHg and 74.9, respectively. During the two-year follow-up, 14% and 18% of the participants increased, respectively, the SBP and DBP, while 15% and 19% of the participants decreased, respectively, the SBP and DBP. We did not find significant associations between food groups and SBP. On the other hand, for each 1% increase in food consumption U/MP/CI and UPF there was, respectively, -0.05 mmHg decrease and +0.05 mmHg increase in DBP over time. Furthermore, the percentage increase in the caloric contribution of U/MP/CI in food consumption decreased the risk of increasing the DBP (RR = 0.56; CI 95% = 0.35-0.90). On the other hand, the percentage increase in the caloric contribution of UPF in food consumption increased the risk of increasing the DBP (4th quintile – RR = 2.02; CI 95% = 1.28-3.18; 5th quintile – RR = 1.75, CI 95 % = 1.10- 2.79). Using the JNC's diagnostic criteria, 230 new cases of hypertension out of 1.868 participants (66/1.000 person-years) were identified. In this case, we did not find significant associations between exposure and outcome too. However, according to the ACC/AHA criteria, 373 new cases of hypertension out of 1.241 participants (160/1.000 person-years) were identified. The highest consumption of food U/MP/CI and UPF was associated, respectively, with reduction (RR = 0.72; CI 95% = 0.52-0.98) and increase (RR = 1.35; CI 95 % = 1.01-1.81) of the risk of hypertension. Conclusions: participants had a high incidence of hypertension, although they are young adults with a high level of education. The highest percentage of caloric contributions to the diet of foods considered healthy (U/MP/CI) and unhealthy (UPF), decreased and increased, respectively, the risk of increased DBP and the incidence of hypertension.